Qualitative Assessment of Undergraduate Nursing Students' Perceptions of Combined Virtual Reality and Group Discussion Learning Interventions: A Focus Group Study - Yuzo Kuwabara; Ai Ogata; Takami Tanaka; Tomoko Nishida; Ikumi Sasaki (Evidence-Based Nursing Research)
Context: The coronavirus disease 2019 (COVID-19) pandemic has forced major changes in the learning environment. The author’s institution created virtual reality (VR) learning content to enhance readiness for on-the-job training students by allowing them to enter situations and circumstances beyond traditional learning, experience simulations of target individuals, and think about the nursing assistance needed. The education combined VR and 360-degree video content with group discussions to increase learning depth. A qualitative analysis of the evaluations from the participating students’ perception was performed to obtain suggestions for future educational methods.